A descriptive-comparative study of performance characteristics in futsal players of different levels - Naser, N.; Ali, A. (Journal of Sports Sciences, 2016)
Despite the increasing popularity of futsal, there is little information on performance characteristics of players. We aimed to determine the validity and reliability of a futsal shooting test and to evaluate and compare performance characteristics of three futsal playing levels. Twenty-four males (n = 8 elite, n = 8 semi-elite, n = 8 social) completed two trials to examine the reliability of the Massey Futsal Shooting Test (MFST) and to compare various fitness characteristics between groups. MFST time taken (P = 0.010), shot speed (P < 0.001) and points scored per shot (P < 0.001) were better for elite relative to social players. Test-retest reliability was acceptable for all groups, but it was most repeatable in elite players. Loughborough Soccer Passing Test performance was better in elite relative to social players (P = 0.004). There were no differences in countermovement-jump height between groups. Elite players ran faster over 5 m than both semi-elite (P = 0.043) and social (P = 0.002) and faster than the social players through 10 m (P = 0.028) and 20 m (P = 0.026). Distance covered in the Futsal Intermittent Endurance Test was higher in elite relative to semi-elite (P = 0.005) and social (P < 0.001) groups. The MFST is a valid and reliable protocol to assess futsal shooting-skill performance; elite players have superior shooting and passing skill and have greater sprinting and intermittent-running ability.